PANTONALITY GENERALISED: BEN JOHNSTON'S ARTISTIC RESEARCHES IN EXTENDED JUST INTONATION. (17th April 2015) - Sabat, Marc
Abstract This article explores the use of innovatory tonal relations in the music of the American composer Ben Johnston (b. 1926). Johnston's use of a microtonal tuning system employing scales and intervals in extended just intonation is described, and passages from several of his compositions (especially String Quartets nos 2 and 5) are analysed to show the use of these pitch resources in practice. The article also situates Johnston's contribution in the context of older theories of harmony and the mechanics of pitch perception.